Minimizing target interference in PK immunoassays: new approaches for low-pH-sample treatment. (August 2013) - Partridge, Michael A; Pham, John; Dziadiv, Olena; Luong, Onson; Rafique, Ashique; Sumner, Giane; Torri, Albert
Background: Quantitating total levels of monoclonal antibody (mAb) biotherapeutics in serum using ELISA may be hindered by soluble targets.Results: We developed two low-pH-sample-pretreatment techniques to minimize target interference. The first procedure involves sample pretreatment at pH <3.0 before neutralization and analysis in a target capture ELISA. Careful monitoring of acidification time is required to minimize potential impact on mAb detection. The second approach involves sample dilution into mild acid (pH ∼4.5) before transferring to an anti-human capture-antibody-coated plate without neutralization. Analysis of target–drug and drug–capture antibody interactions at pH 4.5 indicated that the capture antibody binds to the drug, while the drug and the target were dissociated. Using these procedures, total biotherapeutic levels were accurately measured when soluble target was >30-fold molar excess.Conclusion: These techniques provide alternatives for quantitating mAb biotherapeutics in the presence of a target when standard acid-dissociation procedures are ineffective.